2013
DOI: 10.1021/ja4040472
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Energetic Basis of Carbohydrate–Aromatic Packing Interactions in Proteins

Abstract: Carbohydrate-aromatic interactions mediate many biological processes. However, the structure–energy relationships underpinning direct carbohydrate–aromatic packing in aqueous solution have been difficult to assess experimentally and remain elusive. Here, we determine the structures and folding energetics of chemically synthesized glycoproteins to quantify the contributions of the hydrophobic effect and CH–π interactions to carbohydrate–aromatic packing interactions in proteins. We find that the hydrophobic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(144 citation statements)
references
References 54 publications
6
138
0
Order By: Relevance
“…These residues are conserved in Pf-Avr4, with the exception of Tyr-74, which in Pf-Avr4 is replaced with a tryptophan (Trp-97) ( Figure 3C), a similar but slightly bulkier aromatic residue. Aromatic residues are fundamental components of the protein-carbohydrate binding mechanism, as they are involved in hydrophobic stacking interactions and offer many coordination points for contact with the sugar ligand (Boraston et al, 2004;Chen et al, 2013;Hudson et al, 2015). In this respect, Pf-Avr4 has a third tryptophan (Trp-88), in addition to Trp-94 and Trp-97, located in the putative ChtBD that could potentially participate in the Pf-Avr4-chitin interaction.…”
Section: Structure-based Analysis Positions Pf-avr4's Chitin-binding mentioning
confidence: 99%
“…These residues are conserved in Pf-Avr4, with the exception of Tyr-74, which in Pf-Avr4 is replaced with a tryptophan (Trp-97) ( Figure 3C), a similar but slightly bulkier aromatic residue. Aromatic residues are fundamental components of the protein-carbohydrate binding mechanism, as they are involved in hydrophobic stacking interactions and offer many coordination points for contact with the sugar ligand (Boraston et al, 2004;Chen et al, 2013;Hudson et al, 2015). In this respect, Pf-Avr4 has a third tryptophan (Trp-88), in addition to Trp-94 and Trp-97, located in the putative ChtBD that could potentially participate in the Pf-Avr4-chitin interaction.…”
Section: Structure-based Analysis Positions Pf-avr4's Chitin-binding mentioning
confidence: 99%
“…For example, in GlcNAc and other glucose-derived monosaccharides, the α-face of the pyranose ring is formed by the axial CH bonds, creating a non-polar surface (Figure 2c, d). Burial of this hydrophobic surface through interactions with hydrophobic protein side chains is energetically favorable, but glycan–protein hydrophobic interactions tend to be less favorable than protein–protein hydrophobic interactions because it is difficult to bury the non-polar surfaces without affecting the access of adjacent polar surfaces to water 24, 25 . As previously noted 18 , a good example of a stabilizing hydrophobic glycan–protein interaction is in human chorionic gonadotropin, wherein the α-face of the first GlcNAc residue (GlcNAc1) of the glycan is buried in a pocket formed by Pro24, Ile25, and Leu26 (Figure 2c) 26 .…”
Section: Intrinsic Influences Of N-glycans On Glycoproteostasismentioning
confidence: 99%
“…Aromatic residues at the n-2 positions relative to glycosylation sites on the polypeptide backbone resulted in increased glycan occupancy but also reduced the efficiency of glycan trimming. The authors suggested that the presence of the n-2 aromatic residue resulted in the formation of a reverse turn as a result of hydrophobic stacking between the aromatic residue and the nonpolar face of the adjoining glycan core GlcNAc residue (49). These interactions presumably would compete with steric access for binding to the cleft in the GH47 α-mannosidases and would lead to less efficient mannose cleavage.…”
Section: Implications For Processing Of Oligomannose Glycans In the Smentioning
confidence: 99%